OPTIMALISASI FUNGSI INTELKAM DALAM MEMBEBRIKA EARLY DETECTION TERHADAP MASALAH PENCEMARAN LINGKUNGAN DIWILAYAH KARAWANG - Bagas Tritantio Sanjaya (Police Studies Review, 2017)
The background of the problem comes because the cases of environmental pollution in the Karawang region have increased and are relatively high. Not only that, there are other impacts arising from the problem of environmental pollution, namely the existing social problems that require the task of intelligence in providing early detection. This study aims to determine the early detection of the impact caused by the problem of environmental pollution in the Karawang region, whether it is already optimal by Unit II Socio-Economic, factors that influence the optimization of the implementation of early detection and how to optimize it. This study uses a qualitative approach using descriptive analytical data analysis techniques from observations, interviews and document studies conducted. The theoretical basis used in this study is the optimization theory, the theory of the intelligence rotation wheel (RPI), the concept of early detection, the concept of 6M model analysis, the concept of SWOT analysis and the concept of environmental pollution. The results found that the implementation of early detection analyzed from Perkabik No. 1 of 2013 as a whole was not optimal because there were still shortcomings in the implementation of the field from the planning stage to the presentation. Factors that hamper optimization in terms of quantity and quality of human resources, preliminary data used, how to carry out tasks and target tasks of Unit II of the Karawang Police Intelligence Unit. The conclusion of the implementation of the early detection of the Unit II Socio-Economic Intelligence Unit of the Karawang Regional Police on the problem of environmental pollution in the Karawang region as a whole has not been running optimally. Constructive advice includes suggestions to further optimize the quantity and quality of personnel as well as the implementation of tasks in early detection by increasing the competencies and needs of members, completing the organizational structure and organizational position and overseeing the implementation of the duties of members in the field. Keywords: Optimization of Early Detection of Unit II Socio-Economic, Environmental Pollution Problems.